Novel electrotactile brain-computer interface with somatosensory event-related potential based control - Savić, Andrej M.; Novičić, Marija; Ðorđević, Olivera; Konstantinović, Ljubica; Miler-Jerković, Vera (Frontiers in Human Neuroscience, 2023)
Objective. A brain computer interface (BCI) allows users to control external devices using non-invasive brain recordings, such as electroencephalography (EEG). We developed and tested a novel electrotactile BCI prototype based on somatosensory event-related potentials (sERP) as control signals, paired with a tactile attention task as a control paradigm. Approach. A novel electrotactile BCI comprises commercial EEG device, an electrical stimulator and custom software for EEG recordings, electrical stimulation control, synchronization between devices, signal processing, feature extraction, selection and classification. We tested a novel BCI control paradigm based on tactile attention on a sensation at a target stimulation location on the forearm. Tactile stimuli were electrical pulses delivered at two proximal locations on the user’ forearm for stimulating branches of radial and median nerves, with equal probability of the target and distractor stimuli occurrence unlike in any other ERP-based BCI design. We proposed a compact electrical stimulation electrodes configuration for delivering electrotactile stimuli (target and distractor) using 2 stimulation channels and 3 stimulation electrodes. We tested the feasibility of a single EEG channel BCI control, to determine pseudo-online BCI performance, in ten healthy subjects. For optimizing the BCI performance we compared the results for two classifiers, sERP averaging approaches, and novel dedicated feature extraction/selection methods via cross-validation procedures. Main results. We achieved a single EEG channel BCI classification accuracy in the range of 75.1% to 88.1% for all subjects. We have established an optimal combination of predefined classification, single trial averaging to obtain sERP and feature extraction/selection methods. Significance. The obtained results demonstrate that a novel electrotactile BCI paradigm with equal probability of attended (target) and unattended (distractor) stimuli and proximal stimulation sites is feasible. This method may be used to drive restorative BCIs for sensory retraining in stroke or brain injury, or assistive BCIs for communication in severely disabled users.